Donation after circulatory death hearts recipients compared to donation after brain death heart recipients have comparable systolic left ventricular function and better myocardial strain at 1 year. (25th November 2020) - Ciarka, A; Page, A; Messer, S; Pavlushkov, E; Tsui, S; Parameshwar, J; Williams, L; Aggraval, B; Large, S
Abstract: Purpose: Cardiac transplantation from donation after circulatory death (DCD) has been implemented at our hospital since February 2015. Despite encouraging results some concerns may be raised about the impact of the warm ischemia and reperfusion injury on the myocardium status at longer follow-up. Therefore, we aimed to analyse systolic performance of the left ventricle at 1 year follow in DCD and donation after brain death (DBD) cardiac recipients, as assessed by echocardiography with myocardial deformation imaging. Methods: We identified 46 consecutive DCD cardiac recipients who were transplanted from February 2015 to August 2018 and we matched them with 46 DBD cardiac recipients. Six and 7 patients from DCD and DBD group, respectively, died in the first-year post transplant. In the remaining patients we have compared the classical echocardiographic measurements as well as global longitudinal strain (GLS) and global circumferential strain (GCS) at 1-year follow-up. Results: DCD and DBD patients did not present with differences in terms of classical echocardiographic parameters of left ventricular (LV) structure and systolic function at one-year follow-up. LVEDV was similar in DCD and DBD patients (101±24 vs. 95±32 ml, p=0.4 respectively), as well as LVESV (42±13 vs. 42±16 ml, p=0.9, respectively), LV ejection fraction (58±6 vs. 56±8%, p=0.22) and LV mass (156±39 vs. 163±38 gr, p=0.2, respectively). In contrast, myocardial deformation parameters, such as GLS and GCS, were better in DCD than in DBD (16.1 vs. −14.5%, p<0.01; and −25.2 vs. 22.3%, p<0.05, respectively). The diastolic LV function parameters were similar in DCD and DBD group, as evidenced by E wave velocity, A wave velocity and deceleration time of mitral inflow, however E over E prime was lower in DCD than in DBD recipients (7.7±8.7, p<0.05). Fractional area change of the right ventricle was higher in DCD in comparison with DBD (46±7 vs. 40±7%, p<0.01) while right atrial volume index was lower in DCD than in DBD (25±8 vs. 29±9 ml/m 2, p<0.01). Other parameters of RV function (systolic excursion of the tricuspid annulus, TAPSE) were similar in both groups. Conclusion: DCD and DBD heart recipients present with similar systolic LV function at 1-year follow, as assessed by classical echocardiographic parameters. DCD cardiac recipients have better myocardial deformation parameters as assessed by the speckle tracking, better systolic right ventricular function and lower filling pressures of the left ventricle. Funding Acknowledgement: Type of funding source: None